Association of Seed Borne Mycoflora With Sunflower Seeds (Journal of Plant Disease Sciences, 2019)
Sunflower (Helianthus annus L.) is major edible oil seed crop after soybean and groundnut. India is the largest grower of sunflower with an area of 0.90 million hectares, production of 0.62 million tones and the average productivity of 696 kg/ha. Important sunflower growing states in the country are Karnataka, Andhra Pradesh, Maharashtra, Tamil Nadu, Bihar, Punjab, Haryana and Uttar Pradesh. Almost 50 % of area and production is accounted for by Karnataka followed by Andhra Pradesh and Maharashtra. In Maharashtra sunflower is cultivated on an area of 0.20 million hectares, and production of 0.11 million tonnes with an average productivity of 677 kg/ha. (Anonymous,2011). In Vidarbha region sunflower is cultivated on an area of 0.084 lakh hectares, production of 0.027 lakh tones and the average productivity of 322 kg/ha. (Annual progress report 2014-15, AICRP on sunflower). In vidarbha region of Maharashtra, the disease often appears in epidemic form depending upon the weather conditions and causes heavy damage to the crop. Sunflower suffers from many diseases caused by fungi, bacteria, and viruses. Sunflower is the known host of more than 30 pathogens mostly fungi which under certain climatic condition may impair the normal physiology of the plant, so that yield and oil quality are reduced significantly.
Keywords: Alternaria; sunflower; seed; Mycoflora; transmission